Effect of Diagnostic Biopsy Practice Location on Grade/Volume Reclassification in Active Surveillance for Prostate Cancer: A Multicenter Analysis from the Canary PASS Cohort. Issue 5 (25th September 2021) - Waisman Malaret, Adrian J.; Chang, Peter; Newcomb, Lisa; Faino, Anna; Zheng, Yingye; Zhu, Kehao; McKenney, Jesse K.; Brooks, James D.; Dash, Atreya; Ellis, William J.; Filson, Christopher P.; Gleave, Martin; et al.
Abstract: Introduction: We analyzed the Canary Prostate Cancer Active Surveillance (PASS) cohort to determine if patients who had diagnostic biopsy at an off-site practice were at higher risk of reclassification than those having their diagnostic biopsy at a PASS site. Methods: Participants were prospectively enrolled at 10 academic institutions. We included patients with Gleason score 6 at diagnostic biopsy, <34% positive cores and a first surveillance biopsy in a PASS site <2 years after diagnosis. We dichotomized our population based on diagnostic biopsy location (on-PASS site vs off-PASS site) and used multivariable logistic regression to evaluate association with reclassification at first surveillance biopsy after controlling for possible confounders. We used Fisher's exact test to compare rates of definitive prostate cancer treatment by diagnostic biopsy location. Results: Out of 1, 648 participants in PASS, 906 met the eligibility criteria and were analyzed. Of 519 men who had off-site diagnostic biopsy, 102 (20%) had grade/volume reclassification compared to 72 (19%) of 399 patients who had on-site diagnostic biopsy. After controlling for potential confounders, location of diagnostic biopsy was not significantly associated with grade/volume reclassification (OR 1.32, IQR 0.91–1.92; p=0.141). Participants with an off-site diagnostic biopsy were more likely to elect definitive treatment than participants with an on-site diagnostic biopsy (17%, IQR 14–20 vs 14%, IQR 10–17 within 1 year after first surveillance biopsy; p <0.01). Conclusions: In this evaluation of a large multicenter active surveillance cohort, diagnostic biopsy location was not associated with significant differences in grade/volume reclassification on confirmatory biopsy at academic institutions.